A Novel Imaging System Distinguishes Neoplastic from Normal Tissue During Resection of Soft Tissue Sarcomas and Mast Cell Tumors in Dogs. Issue 6 (9th June 2016) - Bartholf DeWitt, Suzanne; Eward, William C.; Eward, Cindy A.; Lazarides, Alexander L.; Whitley, Melodi Javid; Ferrer, Jorge M.; Brigman, Brian E.; Kirsch, David G.; Berg, John
Abstract : Objective: To assess the ability of a novel imaging system designed for intraoperative detection of residual cancer in tumor beds to distinguish neoplastic from normal tissue in dogs undergoing resection of soft tissue sarcoma (STS) and mast cell tumor (MCT). Study Design: Non‐randomized prospective clinical trial. Animals: 12 dogs with STS and 7 dogs with MCT. Methods: A fluorescent imaging agent that is activated by proteases in vivo was administered to the dogs 4–6 or 24–26 hours before tumor resection. During surgery, a handheld imaging device was used to measure fluorescence intensity within the cancerous portion of the resected specimen and determine an intensity threshold for subsequent identification of cancer. Selected areas within the resected specimen and tumor bed were then imaged, and biopsies (n=101) were obtained from areas that did or did not have a fluorescence intensity exceeding the threshold. Results of intraoperative fluorescence and histology were compared. Results: The imaging system correctly distinguished cancer from normal tissue in 93/101 biopsies (92%). Using histology as the reference, the sensitivity and specificity of the imaging system for identification of cancer in biopsies were 92% and 92%, respectively. There were 10/19 (53%) dogs which exhibited transient facial erythema soon after injection of the imaging agent which responded to but was not consistently prevented by intravenous diphenhydramine. Conclusion: A fluorescence‐based imaging system designed for intraoperative use can distinguish canine soft tissue sarcoma (STS) and mast cell tumor (MCT) tissue from normal tissue with a high degree of accuracy. The system has potential to assist surgeons in assessing the adequacy of tumor resections during surgery, potentially reducing the risk of local tumor recurrence. Although responsive to antihistamines, the risk of hypersensitivity needs to be considered in light of the potential benefits of this imaging system in dogs.